2009
DOI: 10.3144/expresspolymlett.2009.69
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-g-polyaniline: a creatine amidinohydrolase immobilization matrix for creatine biosensor

Abstract: Abstract.A novel matrix composed of chitosan-graft-polyaniline (CHIT-g-PANI) was electrochemically prepared to investigate the immobilization of creatine amidinohydrolase (CAH). CAH enzyme was covalently immobilized with the CHIT-g-PANI matrix using glutaraldehyde as a linker. The resulting CAH/CHIT-g-PANI biomatrix was characterized with Fourier transform infrared spectroscopy (FTIR), atomic force microscopy (AFM), contact angle measurement and cyclic voltammetry (CV) taking CHIT-g-PANI as a reference. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Conducting form of PANI is described by band at 1237 cm -1 [10,46]. The bands at 796 and 1731 cm -1 were corresponding to an out-of-plane bending vibration of C-H on para-disubstituted rings and carboxyl groups, respectively [10,47,48]. It has been reported that the band at 1110 cm -1 to be a measure of the degree of the delocalization of electrons and is also revealing of high conductivity.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…Conducting form of PANI is described by band at 1237 cm -1 [10,46]. The bands at 796 and 1731 cm -1 were corresponding to an out-of-plane bending vibration of C-H on para-disubstituted rings and carboxyl groups, respectively [10,47,48]. It has been reported that the band at 1110 cm -1 to be a measure of the degree of the delocalization of electrons and is also revealing of high conductivity.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…5C, component 2) can appear due to hydrogen bonding or covalent bonding between zein and PANI, in particular NH 2 and OH groups in zein molecules. These types of interactions were reported for chitosan [19,20] and polysaccharide [10] in their combination with PANI. The N(1s) peaks were also seen in all the samples.…”
Section: Resultsmentioning
confidence: 83%
“…The second way was attempted with the aim to study some possible interactions between zein and PANI reported already for some other products containing PANI prepared by in situ oxidative polymerisation, e.g. polysaccharide-PANI Downloaded by [University of Tasmania] at 21:17 13 October 2014 [10] and chitosan-PANI [19,20] because such an order of mixing ingredients is more favorable for a grafting polymerisation rather than formation of homopolymer.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of pH, temperature, and time on the CAH enzyme activity within the matrix was studied. The Michaelis -Menten constant and apparent activity for the CAH enzyme were calculated to be 0.51 mM and 83.59 mg cm − 2 , which was attributed to the fact that the chitosan -graft -PANI matrix had a high affi nity to immobilize CAH enzyme [30] . MWNTs, Pt -NPs, and a sol -gel of chitosan -silica organic -inorganic hybrid composite was used to develop a glucose biosensor.…”
Section: Chitosan Nanocomposite -Based Conductimetric Biosensorsmentioning
confidence: 99%